2018
DOI: 10.1007/s12264-018-0296-5
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte Plasticity in the Brain

Abstract: Cerebral pericytes are perivascular cells that stabilize blood vessels. Little is known about the plasticity of pericytes in the adult brain in vivo. Recently, using stateof-the-art technologies, including two-photon microscopy in combination with sophisticated Cre/loxP in vivo tracing techniques, a novel role of pericytes was revealed in vascular remodeling in the adult brain. Strikingly, after pericyte ablation, neighboring pericytes expand their processes and prevent vascular dilatation. This new knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 145 publications
0
34
0
Order By: Relevance
“…The perivascular niches are themself complex and heterogeneous composed by multiple other cell types in addition to endothelial cells in the neurogenic niches, such as perivascular astrocytes, perivascular neurons [106,110,111], perivascular macrophages [112114], perivascular adventitial cells [115], perivascular fibroblasts [116], microglia [117], vascular smooth muscle cells [118], and pericytes subsets [119]. Interestingly, pericytes from several peripheral tissues have been shown to behave as stem cells [78,120139,189,190], generating other cell types, and also to regulate the behavior of other stem cells, as hematopoietic stem cells in their niches [87,88,140144]. Although growing evidence also shows that central nervous system pericytes alter their characteristics following stimuli and develop sternness [145149], whether pericytes are an essential component of neural stem cell niche, and what are their exact roles remains unexplored.…”
Section: Perivascular Neural Stem Cell Nichementioning
confidence: 99%
“…The perivascular niches are themself complex and heterogeneous composed by multiple other cell types in addition to endothelial cells in the neurogenic niches, such as perivascular astrocytes, perivascular neurons [106,110,111], perivascular macrophages [112114], perivascular adventitial cells [115], perivascular fibroblasts [116], microglia [117], vascular smooth muscle cells [118], and pericytes subsets [119]. Interestingly, pericytes from several peripheral tissues have been shown to behave as stem cells [78,120139,189,190], generating other cell types, and also to regulate the behavior of other stem cells, as hematopoietic stem cells in their niches [87,88,140144]. Although growing evidence also shows that central nervous system pericytes alter their characteristics following stimuli and develop sternness [145149], whether pericytes are an essential component of neural stem cell niche, and what are their exact roles remains unexplored.…”
Section: Perivascular Neural Stem Cell Nichementioning
confidence: 99%
“…The skin is composed by a complex microenvironment which contains several constituents, in addition to dendritic cells and CD8+ T cells: other immune cells, various types of stromal cells, innervations, stem cells, Schwann cells, and extracellular matrix proteins . This complex mixture of cells cooperate to perform the necessary functions for the skin healing, and the interplay between these distinct components of the cutaneous microenvironment will define the success of skin repair .…”
Section: Perspectives/future Directionsmentioning
confidence: 99%
“…In addition, Birbrair et al[52] reported that nestin + /NG2 + type-2 pericytes have NG2 + glia-like traits. However, NG2 + glia is identical to OPCs[53], and both pericytes and OPCs express common markers, including NG2 and PDGFRα[54]. Thus, the precise connection between iNSPCs and resident glia should be determined in further studies (Figure 1).…”
Section: Brain Pericytes Following Ischemia: Do They Function As Nspcs?mentioning
confidence: 99%